Pautas de validez de los contenidos en las clases de ciencias: una aproximación al problema de los criterios de validez del conocimiento escolar - Martínez Rivera, Carmen Alicia; Rivero García, Ana (Revista Científica, 2011)
This it is a document with which one looks for to contribute to the debate with respect to which they are the criteria from which one affirms that something is or nonvalid in the scholastic processes, from the point of view of the professors. The support of this writing becomes from the results of two investigations (Martinez, 2000; Martinez, 2005)4, in individual exposes the study of case of professor Rosa, in whom it appears the category criteria of validity, like of great potentiality in the Construction of the scholastic knowledge in the classes of sciences.